Implementation of Education Financing Policy from the Perspective of School-Based Management in Primary Schools - Riski Maulina; Suryani Suryani; Siti Tabiatun; Irwati Irwati; Sonny Muhammad Ikhsan Mangkuwinata (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Education financing is a strategic component in ensuring the sustainability of school programs, improving learning quality, and supporting the provision of facilities and infrastructure. At the elementary school level, financing plays a crucial role as it forms the foundation for students’ academic, character, and social development. This study aims to analyze the implementation of education financing policy from the perspective of School-Based Management (SBM), focusing on budget planning, fund utilization, financial transparency, supervision, and stakeholder involvement. The research employed a descriptive quantitative approach using a survey method. Data were collected through questionnaires distributed to principals, school treasurers, teachers, and school committee members who are directly involved in financial management. The data were analyzed using descriptive statistics in percentage form. The findings indicate that the implementation of education financing policy in elementary schools has generally been carried out well. This is reflected in participatory budget planning, appropriate fund utilization based on priority needs, regular financial reporting, and the involvement of school committees in supervision. However, several challenges remain, including limited financial administrative competence, uneven technical understanding of budget management, and a shortage of administrative personnel. Therefore, strengthening the managerial and financial competencies of school stakeholders is essential to improve the effectiveness, transparency, and accountability of education financing policy implementation in elementary schools.